2005
DOI: 10.1254/jphs.sc0050105
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Releaser Attenuates β-Amyloid (1 – 42)-Induced Memory Impairment in Mice

Abstract: Abstract. Accumulating evidence indicates that growth hormone (GH) might be effective at preventing the development of Alzheimer's disease. However, exogenous GH treatment has exhibited side effects for clinical application; thus supplementation with amino acids to promote the release of GH could be a possible alternative treatment. In this study, mice that were fed with a diet of GH-releasing supplements had significantly attenuated memory impairments and hippocampal changes in the acetylcholinesterase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…We have previously reported the positive effects of the GH-releaser diet on Aβ(1-42)-induced cognitive impairment in the water maze and passive avoidance tests in mice (3). In this study, learning and memory capacities were evaluated with a conditioned-fear learning test (5).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…We have previously reported the positive effects of the GH-releaser diet on Aβ(1-42)-induced cognitive impairment in the water maze and passive avoidance tests in mice (3). In this study, learning and memory capacities were evaluated with a conditioned-fear learning test (5).…”
mentioning
confidence: 95%
“…As oral administration of some amino acids (e.g., arginine, glutamine, glycine, and lysine) increases the release of endogenous GH (2), supplementation may be a useful pharmacological intervention. We have previously demonstrated that a "GH-releaser diet" significantly prevented β-amyloid (Aβ) (1-42)-induced learning impairment (3). In this study, we examined whether the IGF-1 receptor was involved in the GH-releaser diet-mediated pharmacological action of Aβ(1-42)-induced toxicity in mice.…”
mentioning
confidence: 99%
“…The evidence suggests that a functional link may exist between the cholinergic system and growth hormone (GH) secretion. For example, the secretion of GH from the pituitary is enhanced by acetylcholinesterase inhibitor (pyridostigmine) 7 and a primary mediator of growth hormone/insulin-like growth factor-1 (IGF-1) or GH-releasing hormone, which can stimulate secretion of acetylcholine from rat cortical slices and the hippocampus respectively 8,9 . It has recently been shown that age-related reductions in plasma GH, known as somatopause, is associated with increased incidence of cognitive impairment and AD, and can be compensated through GH treatment 10,11 .…”
mentioning
confidence: 99%
“…It has recently been shown that age-related reductions in plasma GH, known as somatopause, is associated with increased incidence of cognitive impairment and AD, and can be compensated through GH treatment 10,11 . Various central effects of GH, such as cell genesis, neurogenesis 12 and angiogenesis 13 , suggest that GH administration may be effective in preventing the development or progression of AD 9,14,15 . Molecular mechanisms of improved cognitive functions after GH treatment are not known but may be due to the direct impact of the hormone on the brain.…”
mentioning
confidence: 99%
“…8 Growth hormone releaser, such as arginine, glutamine, glycine, and lysine, has been found to increase endogenous GH release, and to attenuate the b-amyloid peptide (Ab)-induced memory impairment in mice. 9 In addition, there is substantial evidence that an increased availability of hypothalamic acetylcholine can stimulate GH release, probably via suppression of somatostatin. Cholinesterase-inhibitors, such as rivastigmine and donepezil, in AD therapy have also been found to elicit GH secretion and enhance a GH response to GH-releasing hormone.…”
Section: Introductionmentioning
confidence: 99%